EMPOWERING CAREER CHOICES: THE EFFECTIVENESS OF MOTIVATIONAL INTERVIEWING IN GROUP COUNSELING FOR HIGH SCHOOL STUDENTS' DECISION-MAKING SKILLS - Srianturi, Yanuari; Distira, Riski Putra Ayu; Nurkholidah, Enik (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Career decision-making is a process of selecting alternatives that must be undertaken by each individual by considering their abilities, potential, talents, and interests in accordance with their field. This skill is essential for senior high school students to determine their career direction, set clear goals, and commit to implementing the decisions they make. This study aims to describe the career decision-making abilities of students and to examine the effectiveness of group counseling using the Motivational Interviewing technique in improving these abilities. The research employed a quantitative method with a pre-experimental design, specifically a one-group pretest-posttest approach. The sampling technique was purposive sampling, involving 8 respondents out of a total of 94 eleventh-grade students. Feasibility tests conducted by experts and practitioners indicated that the model met the scientific criteria for guidance and counseling and was deemed suitable for use by school counselors. The trial results showed an increase in career decision-making scores from 163 (pretest) to 206.5 (posttest), representing a 26.7% improvement. These findings demonstrate that the Motivational Interviewing technique in group counseling is effective as an intervention to significantly enhance students’ career decision-making abilities. It is recommended that school counselors consider adopting this technique as part of their career guidance programs to support students in making well-informed career choices.